Aceh post-peace agreement: new conflicts and transactional politics - Cut Maya Aprita Sari; Kartini Aboo Talib @ Khalid; Shazlin Amir Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2023)
The conflict between the Free Aceh Movement (GAM) and the Indonesian government since 1976 ended with the MoU Helsinki peace agreement in 2005. This peace agreement gave the Acehnese hope to experience comprehensive peace. However, peace is not fully realized. The peace agreement led to the transformation of a new conflict that affected the people of Aceh. This study aims to map the six recent disputes that emerged after the MoU Helsinki 2005 and analyze the existence of transactional politics in the six new conflicts in Aceh. This study shows two things using a qualitative approach and transactional political theory. First, after the MoU Helsinki 2005, Aceh experienced six new conflicts, namely: the transformation of GAM into a local political party; conflict and violence in elections; transitional justice conflict; the emergence of armed criminal groups (ACG); Sharia law conflict, and the emergence of Aceh Sumatra National Liberation Front (ASNLF) as a counter-peace movement. Second, the emergence of these six new conflicts cannot be separated from the existence of transactional politics. Aceh’s political elite always prioritizes transactions, patron-client relationships, and government power. The transformation of the conflict in Aceh caused the people of Aceh to continue to live in poverty and unsafe conditions.